Integration of Multicultural Education Values in History Teaching - Setiyonugroho, Ponco; Umasih, Umasih; Kurniawati, Kurniawati (LPPM Undiksha, 2022)
The differences in various things will prove that each individual has a different point of view in looking at the differences that occur in Indonesia. These various views can ultimately trigger the occurrence of inter-ethnic, religious, and cultural innovations that are found in conflict. This study aims to analyze the integration of multicultural education in history learning. This research uses qualitative research with a case study approach. Informants obtained 9 people who were selected using the purposive sampling technique. The method used in data collection uses observation, interviews, and documentation. The instruments used are interview sheets and questionnaires. The technique used to analyze the data is descriptive qualitative analysis. The results show that multicultural integration is a synchronization effort between learning methods. Humans have gender, social status, religion, race, and language differences. The teacher conveys historical material to students about multicultural education through history learning. In addition, there are multicultural values ​​that can be integrated into history learning, including four values, namely tolerance, pluralism, humanism, and democracy. It is concluded that multicultural education is one of the essential concepts that history teachers must master in applying multicultural values ​​to more in-depth historical material, which will give students a high spirit of tolerance in society and the environment.